Limitations and Perspectives on Triplet‐Material‐Based Organic Photovoltaic Devices - Jin, Yingzhi; Zhang, Yanxin; Liu, Yanfeng; Xue, Jie; Li, Weiwei; Qiao, Juan; Zhang, Fengling (Advanced materials (Weinheim), 2019)
Organic photovoltaic cells (OPVs) have attracted broad attention and become a very energetic field after the emergence of nonfullerene acceptors. Long‐lifetime triplet excitons are expected to be good candidates for efficiently harvesting a photocurrent. Parallel with the development of OPVs based on singlet materials (S‐OPVs), the potential of triplet materials as photoactive layers has been explored. However, so far, OPVs employing triplet materials in a bulk heterojunction have not exhibited better performance than S‐OPVs. Here, the recent progress of representative OPVs based on triplet materials (T‐OPVs) is briefly summarized. Based on that, the performance limitations of T‐OPVs are analyzed. The shortage of desired triplet materials with favorable optoelectronic properties for OPVs, the tradeoff between long lifetime and high binding energy of triplet excitons, as well as the low charge mobility in most triplet materials are crucial issues restraining the efficiencies of T‐OPVs. To overcome these limitations, first, novel materials with desired optoelectronic properties are urgently demanded; second, systematic investigation on the contribution and dynamics of triplet excitons in T‐OPVs is necessary; third, close multidisciplinary collaboration is required, as proved by the development of S‐OPVs. To harvest a large photocurrent in bulk‐heterojunction organic photovoltaic cells (OPVs), materials with long‐lifetime triplet excitons are expected to be potential candidates for providing sufficient time for diffusion of excitons to donor/acceptor interfaces. Recent progress of various triplet‐material‐based OPVs (T‐OPVs) is briefly summarized, and performance limitations and strategies to further enhance the performance of T‐OPVs are discussed.